2012
DOI: 10.5267/j.msl.2012.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the management barriers for establishing suggestions system: A case study of educational system

Abstract: Suggestions system is one of the new cooperative management plans, which affects making good decisions, self-confidence and employees occupational approval. The aim of this research is to survey the barriers for establishment of suggestion system. The proposed study designs and distributes a questionnaire among 195 out of 26550 managers who work for educational system in city of Kermanshah, Iran. The primary purpose of this survey is to learn whether lack of accepting any risk on behalf of management team, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, there are many evidences, which indicate that management teams normally attempt to underestand their shortcoming through suggestion systems (Milner et al 1995;Recht & Wilderom, 1998;Heresy & Blanchard, 2001;Anderson, 2004). Nouri and Ahanchi (2012) investigated the barriers of having recommendation systems in education system and focused on management team's shortcomings. They reported that lack of accepting risk among management team is number one barrier in having suggestion system followed by existing conflict between management style and suggestions system and lack of management's belief to suggestions system, weakness in education for suggestions system and fear in management disruption because of having suggestions system.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many evidences, which indicate that management teams normally attempt to underestand their shortcoming through suggestion systems (Milner et al 1995;Recht & Wilderom, 1998;Heresy & Blanchard, 2001;Anderson, 2004). Nouri and Ahanchi (2012) investigated the barriers of having recommendation systems in education system and focused on management team's shortcomings. They reported that lack of accepting risk among management team is number one barrier in having suggestion system followed by existing conflict between management style and suggestions system and lack of management's belief to suggestions system, weakness in education for suggestions system and fear in management disruption because of having suggestions system.…”
Section: Introductionmentioning
confidence: 99%